Pengaruh Risiko Bisnis, Growth Opportunity dan Kepemilikan Manajerial terhadap Struktur Modal : (Studi Empiris Perusahaan Property & Real Estate Yang Terdaftar Di Bursa Efek Indonesia Tahun 2018-2022) - Yulia Tantri (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
This study aims to determine the influence of Business Risk, Growth Opportunity, and Managerial Ownership on Capital Structure. Business Risk is measured using EBIT divided by total assets. Growth Opportunity is measured by using total assets in the current period minus total assets in the previous period, and divided by total assets in the previous period. Managerial ownership is measured by the number of shares owned by the managerial party (manager and directors) divided by the total outstanding shares. Meanwhile, the Capital Structure is measured using the Debt Equity Ratio (DER). The population in this study is property & real estate sector companies listed on the Indonesia Stock Exchange for the 2018-2022 period. The number of samples in this study was 16 with a 5-year observation method in the 2018-2022 period and the number of financial statements used as samples in this study amounted to 80, which was obtained through the purposive sampling method. The type of data in this study is secondary data with quantitative research methods. The analysis technique used was panel data regression analysis with a significance level of 5%. This study was processed using eviews 12 software and showed the results that (1) Business risk had a significant negative effect on capital structure, (2) Growth opportunity did not have a significant effect on capital structure, (3) Managerial ownership did not have a significant effect on capital structure.